Student’s learning experiences in an online learning environment using Garrison's Col framework - Titi Chandrawati; Laksmi Dewi; Nurhikmah H; Afriani Afriani; Fajar Arwadi; Heni Safitri; Faaizah Shahbodin (Inovasi Kurikulum, 2024)
This study was conducted to examine the implementation of online learning in distance education utilizing the Community of Inquiry (CoI) framework, as introduced by Garrison. The CoI framework consists of three core elements essential in implementing online learning: social presence, cognitive presence, and teaching presence. These components are crucial for the success of online learning modalities. This is due to the nature of online learning, where instructors and learners are not present at the exact location or time, necessitating a 'binding element' in the educational process to ensure effective management of learning activities. Consequently, this research involved distributing questionnaires to 317 participants enrolled in online courses at Universitas Terbuka Indonesia. The results obtained from this study were classified as high, indicating that all three CoI elements achieved high ratings. Specifically, the aspect of cognitive presence was dominated by resolution capabilities. In social presence, the open communication capacity scored higher than the affective and cohesive components. Meanwhile, facilitating discourse was rated higher in the teaching presence domain than instructional design, organization, and direct instruction. Based on these findings, it can be concluded that learning across these three aspects is considerably high in the students' online learning experiences.   Abstrak Penelitian ini dilakukan untuk mengetahui bagaimana pembelajaran daring pada pembelajaran jarak jauh melalui pendekatan Community of Inquiry (CoI) framework yang diperkenalkan oleh Garrison. CoI memiliki tiga unsur yang menjadi perhatian dalam implementasi pembelajaran daring, yaitu social presence, cognitive presence, dan teaching presence. Ketiga unsur ini menjadi komponen penting dalam keberhasilan pembelajaran yang bersifat daring. Mengapa demikian? Karena pembelajaran daring adalah pembelajaran dimana antara pengajar dan peserta tidak berada pada tempat dan waktu yang bersamaan. Sehingga jika tidak ada “pengikat” dalam proses pembelajaran tersebut akan sulit untuk mengontrol pelaksanaan pembelajaran. Oleh karena itu, pada penelitian ini dilakukan penyebaran kuesioner kepada 317 peserta yang mengikuti perkuliahan pembelajaran daring di Universitas Terbuka Indonesia. Hasil yang diperoleh dari penelitian ini dalam kategori tinggi. Hal ini menunjukkan bahwa dari ketiga unsur CoI berada pada kategori tinggi, sspek cognitive presence didominasi oleh kemampuan resolution. Pada aspek social presence kemampuan open communication tinggi dibandingkan affective dan cohesive. Sedangkan pada aspek teaching presence facilitating discourse memiliki nilai lebih tinggi dibandingkan instructional design and organization dan direct instruction. Berdasarkan data tersebut dapat disimpulkan bahwa kehadiran pembelajaran dari ketiga aspek tersebut cukup tinggi dalam pembelajaran daring yang dialami oleh siswa. Kata Kunci: community of Inquiry; evaluasi pengalaman belajar mahasiswa; pembelajaran daring